1975
DOI: 10.1128/jb.121.3.863-872.1975
|View full text |Cite
|
Sign up to set email alerts
|

Self-transferable plasmids determining the hemolysin and bacteriocin of Streptococcus faecalis var. zymogenes

Abstract: Strains of Streptococcus faecalis var. zymogenes, designated JH1 and JH3, produced a hemolysin and a bacteriocin. Hemolytic activity was lost from a low percentage of cells grown in broth at either 37 or 45 C. All nonhemolytic (Hly-) variants had lost bacteriocin activity (Bcn-), and those from strain JH3 had also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 22 publications
3
42
0
1
Order By: Relevance
“…Although we did not study many antibiotic resistant strains, the reason why bacteriocinogenic strains were not drug resistant is of great interest. Since drug resistance and bacteriocinogeny appear to be mediated by plasmids in Streptococcus faecalis (8,9) and Streptococcus pyogenes (17), it might be possible that the drug resistance and bacteriocinogeny in Streptococcus mutans are also coded by the respective plasmids and that these two plasmids are mutually exclusive of each other. Therefore, bacteriocin typings of new antibiotic resistant isolates of this bacterium will be of great future interest.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not study many antibiotic resistant strains, the reason why bacteriocinogenic strains were not drug resistant is of great interest. Since drug resistance and bacteriocinogeny appear to be mediated by plasmids in Streptococcus faecalis (8,9) and Streptococcus pyogenes (17), it might be possible that the drug resistance and bacteriocinogeny in Streptococcus mutans are also coded by the respective plasmids and that these two plasmids are mutually exclusive of each other. Therefore, bacteriocin typings of new antibiotic resistant isolates of this bacterium will be of great future interest.…”
Section: Discussionmentioning
confidence: 99%
“…Localization of the cytolysin determinant to conjugative plasmids was achieved through broth mating experiments (Dunny and Clewell, 1975;Jacob et al ., 1975), and it was also observed that the conjugative plasmid harbouring the cytolysin determinant was pheromone responsive (Dunny et al ., 1978;1979; for a recent review of pheromone plasmid transfer, see Clewell, 1999).…”
Section: Role Of Cytolysin In E Faecalis Infection Pathogenesismentioning
confidence: 99%
“…zymogenes. Since the differentiation of these organisms is based on unstable, plasmiddependent (Jacob et al 1975) haemolytic activity (Deibel 1964) it was decided to group these organisms under Strep. faecalis.…”
Section: Collection and Ident8cation Of Isolatesmentioning
confidence: 99%